Time trend of cadmium intake in Korea - Moon, Chan-Seok (Environ Health Prev Med, 2016)
OBJECTIVES: The aim of this study was to elucidate past and current levels of cadmium (Cd) intake among the general populations in Korea. METHODS: For this purpose, publications reporting dietary intake of cadmium (Cd-D), cadmium concentration in blood (Cd-B) and that in urine (Cd-U) in Korea were retrieved through literature survey for a period from 1975 to 2015. RESULTS: In practice, 9, 21 and 14 articles were available on Cd-D, Cd-B and Cd-U(cr) (Cd-U as corrected for creatinine concentration), respectively. Linear regression analyses of the reported values as a function of years (i.e., the year when each survey was conducted) showed steady decreases in all of the three exposure markers of Cd-D, Cd-B and Cd-U(cr). Factors possibly contributing for the reduction were discussed including the government-set guideline of 0.2 mg/kg for rice and changes in food habits among general populations. CONCLUSIONS: There have been steady decreases in Cd-D, Cd-B and Cd-U(cr). The current estimates for Cd-D, Cd-B and Cd-U(cr) were 6.0–7.4 μg/day, 0.73–0.83 μg/L and 0.60–0.95 μg/g cr, respectively.